Removal of Zn, Pb and Cr in Textile Wastewater Using Rice Husk as a Biosorbent - Muneer, Majid; A. Bhatti, Ijaz; Adeel, Shahid (Asian Journal of Chemistry, 2010)
Biosorption technique has been employed for the treatment of textile processing industrial wastewater using rice husk as biosorbant for the metal binding. The samples were collected from textile-processing units located in the premises of Faisalabad city. The concentration of heavy metals Zn, Pb and Cr were examined using atomic absorption spectrometry. The concentration of these metals were detected in the range of 1.05-5.36, 0.50-2.2 and 0.45-8.33 (ppm), which were higher than the permissible limits recommended by environmental protection agency (EPA), Pakistan. The wastewater samples were treated using rice husk as biosorbant in a continuous flow system using glass column and adsorption capacity was calculated in order to study the adsorption of metals on the biomass. There was a remarkable decrease in the concentration of Zn, Pb and Cr after adsorption, furthermore the other quality parameters such as pH, turbidity, electrical conductivity (EC), total hardness (TH), total dissolved solids (TDS), total suspended solids (TSS), chemical oxygen demand (COD) and dissolved oxygen (DO) were also investigated before and after adsorption. It was found that the concentrations of Zn, Pb and Cr were decreased up to 57, 59 and 58 %, respectively. The metal binding capacity of rice husk for the removal of heavy metals from the wastewater was as Zn < Cr < Pb.